1984
DOI: 10.1577/1548-8659(1984)113<767:cawqsi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Confinement and Water Quality-Induced Stress in Largemouth Bass

Abstract: Plasma values of corticosteroids, glucose, chloride, and osmolality were determined in largemouth bass Micropterus salmoides under various environmental conditions. No differences were observed in quiescent fish due to sex, size, time of day, or the types of holding facilities tested (tanks, raceways, ponds). Differences were observed in plasma glucose, chloride, and osmolality values among fish acclimated to 10, 16, and 23 C. Abrupt temperature changes caused elevations in plasma corticosteroid and glucose co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 0 publications
4
54
1
5
Order By: Relevance
“…Another interesting finding from the Cooke et al (2002) study is that the addition of salt and water conditioners more than doubled the time required for cardiac parameters to normalize. These findings point out an interesting contradiction with others that have found stress to be minimized by the addition of salt, water conditioners, and antibacterial agents (Carmichael et al 1984b;Plumb et al 1988;Swanson et al 1996).…”
Section: Metabolism and Growthcontrasting
confidence: 89%
See 1 more Smart Citation
“…Another interesting finding from the Cooke et al (2002) study is that the addition of salt and water conditioners more than doubled the time required for cardiac parameters to normalize. These findings point out an interesting contradiction with others that have found stress to be minimized by the addition of salt, water conditioners, and antibacterial agents (Carmichael et al 1984b;Plumb et al 1988;Swanson et al 1996).…”
Section: Metabolism and Growthcontrasting
confidence: 89%
“…Confinement can refer to either the entire volume of a small tank (Pankhurst and Sharples 1992;Clearwater and Pankhurst 1997;Carey and McCormick 1998;Hobby et al 2000;Fevolden et al 2003) or to a restricting net placed within the larger volume of a tank (Carmichael et al 1984b;Haux and Sjö beck 1985;Strange and Cech 1992;Ruane et al 1999). In either case, confinement causes fish to be in close proximity to one another where the number of fish or biomass per volume (density) may be the same.…”
Section: Stocking Density and Confinementmentioning
confidence: 99%
“…Fish tested in the raceway were acclimated in submerged holding wells that were opaque and completely dark, while those acclimated in the respirometer were exposed to small amounts of ambient (but not direct) sunlight. Carmichael et al (1984) reported that largemouth bass (Micropterus salmoides) did not become stressed (i.e. hyperglycaemic) when net-confined in the dark, while those tested under lighted conditions showed elevated plasma glucose levels consistent with stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, tournamentcaught fish are held in LWs for up to 8-9 h postcapture, during which they may be subjected to additional stress (Hartley and Moring 1993;Kwak and Henry 1995). Because the effects of sequential stressors tend to be cumulative (Carmichael et al 1984;Barton et al 1986), LW conditions to which fish are confined after being stressed by capture are also likely to affect survival. Schramm et al (2010) found that the survival of Walleyes caught during 14 tournaments spanning the entire open-water Walleye tournament season was correlated with LW temperature and dissolved oxygen (DO) concentration.…”
Section: Tournament Effects On Walleye Survival 869mentioning
confidence: 99%